2000
DOI: 10.1076/1380-3395(200002)22:1;1-8;ft115
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Functioning of Adults with Attention Deficit Hyperactivity Disorder

Abstract: The neuropsychological functioning of adults with Attention Deficit Hyperactivity Disorder (ADHD) was compared to that of healthy controls and individuals with mild psychiatric disorders including attentional complaints. Thirty adults in each group were examined on the Conners' Continuous Performance Test (CPT) and measures of attention, executive function, psychomotor speed, and arithmetic skills. The ADHD group performed lower than healthy controls on most measures. However when compared to the psychiatric g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
84
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 0 publications
15
84
1
2
Order By: Relevance
“…The present studies revealed that adult patients with ADHD off MPH displayed marked deficits of both divergent and (Boonstra et al, 2005;Dinn et al, 2001;Jenkins et al, 1998;Lovejoy et al, 1999;Tucha et al, 2005;Walker et al, 2000). Furthermore, previous studies also found that the number of rule violations on fluency tasks is a less sensitive measure for the differentiation of ADHD adults and healthy participants than the number of correct answers or the total output (Jenkins et al, 1998;Tucha et al, 2005).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The present studies revealed that adult patients with ADHD off MPH displayed marked deficits of both divergent and (Boonstra et al, 2005;Dinn et al, 2001;Jenkins et al, 1998;Lovejoy et al, 1999;Tucha et al, 2005;Walker et al, 2000). Furthermore, previous studies also found that the number of rule violations on fluency tasks is a less sensitive measure for the differentiation of ADHD adults and healthy participants than the number of correct answers or the total output (Jenkins et al, 1998;Tucha et al, 2005).…”
Section: Discussionmentioning
confidence: 78%
“…The limited number of studies examining problem solving abilities in adults with ADHD unfortunately focused only on single aspects of problem solving, such as verbal fluency functions (Dinn et al, 2001;Jenkins et al, 1998;Johnson et al, 2001;Lovejoy et al, 1999;Riccio, Wolfe, Romine, Davis, & Sullivan, 2004;Tucha et al, 2005;Walker et al, 2000;Weyandt, Rice, Linterman, Mitzlaff, & Emert, 1998). Furthermore, these studies have failed to describe the basis and classification of the measures used and their relationship to models of problem solving.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there are only very few studies in adult ADHD that have included clinical comparison groups. The few studies available suggest lack of specificity in adult ADHD as well (Taylor & Miller, 1997 ;Walker et al 2000 ;Epstein et al 2001). It is well known that many other psychiatric disorders are accompanied by EF deficits, such as schizophrenia (Velligan & Bow-Thomas, 1999), and depression (Ottowitz et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, impairments in ECF may be a common denominator in the evolution of maladaptive behaviors, not only in substance abuse but also in other neuropsychiatric disorders such as posttraumatic stress disorder, 37 obsessive-compulsive disorders, 38 and attention-deficit disorder. 39 An understanding of the neural mechanisms involved in executive cognitive control, especially under conditions of conflict, may elucidate the neural substrates involved in a variety of neuropsychiatric disorders. …”
Section: Discussionmentioning
confidence: 99%